Modifikasi Pembangkit Kunci Algoritma RSA Dengan Menerapkan Algoritma Blum Blum Shub (BBS) - Sianturi, Chandra Frenki (Forum Kerjasama Pendidikan Tinggi, 2020)
RSA has two keys, namely public key and secret key. RSA bases its encryption and decryption process on the concepts of prime numbers and modulo arithmetic. Both encryption and decryption keys are integers. The encryption key is not kept secret and given to the public (so called the public key), but the key for decryption is confidential (private key). To find the decryption key, it is done by factoring an integer into its prime factors. Therefore to strengthen the security of the RSA algorithm it is necessary to process the key making by factoring an integer into its prime factors in general. Because this is so common, a key modification to the RSA algorithm needs to be done. Modifications are carried out by using another algorithm that uses random numbers. By entering random numbers, it is considered able to eliminate the possibility of an attacker guessing the results by knowing the algorithm. One of these algorithms is the Blum Blum Shub Algorithm (BBS) algorithm. The purpose of using the Blum Blum Shub (BBS) algorithm is to make the key more difficult to guess, making it difficult for cryptanalysts to read the message or information. Based on the results of the above analysis that the RSA algorithm can be used for key formation by using the Blum Blum Shub algorithm as a key used in the RSA algorithm